The Smaug RNA-Binding Protein Is Essential for microRNA Synthesis During the Drosophila Maternal-to-Zygotic Transition. - Luo, H.; Li, X.; Claycomb, J.M.; Lipshitz, H.D. (G3 : genes - genomes - genetics, 2016)
Metazoan embryos undergo a maternal-to-zygotic transition (MZT) during which maternal gene products are eliminated and the zygotic genome becomes transcriptionally active. During this process, RNA-binding proteins (RBPs) and the microRNA-induced silencing complex (miRISC) target maternal mRNAs for degradation. In Drosophila, the Smaug (SMG), Brain tumor (BRAT), and Pumilio (PUM) RBPs bind to and direct the degradation of largely distinct subsets of maternal mRNAs. SMG has also been shown to be required for zygotic synthesis of mRNAs and several members of the miR-309 family of microRNAs (miRNAs) during the MZT. Here, we have carried out global analysis of small RNAs both in wild-type and in smg mutants. Our results show that 85% of all miRNA species encoded by the genome are present during the MZT. Whereas loss of SMG has no detectable effect on Piwi-interacting RNAs (piRNAs) or small interfering RNAs (siRNAs), zygotic production of more than 70 species of miRNAs fails or is delayed in smg mutants. SMG is also required for the synthesis and stability of a key miRISC component, Argonaute 1 (AGO1), but plays no role in accumulation of the Argonaute family proteins associated with piRNAs or siRNAs. In smg mutants, maternal mRNAs that are predicted targets of the SMG-dependent zygotic miRNAs fail to be cleared. BRAT and PUM share target mRNAs with these miRNAs but not with SMG itself. We hypothesize that SMG controls the MZT, not only through direct targeting of a subset of maternal mRNAs for degradation but, indirectly, through production and function of miRNAs and miRISC, which act together with BRAT and/or PUM to control clearance of a distinct subset of maternal mRNAs.